2015
DOI: 10.1037/stl0000048
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of interteaching and its impact on student learning and satisfaction.

Abstract: This review provides a historical overview of behavioral teaching methods that have demonstrated efficacy across age groups, educational levels, and disciplines. In particular, we focus on a recent behavioral teaching method known as interteaching to highlight its effectiveness as a user-friendly alternative to the traditional classroom lecture. Applications of prior behavioral teaching methods will be briefly highlighted, followed by a more thorough overview of the empirical data to date supporting interteach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 41 publications
1
38
1
Order By: Relevance
“…Zayak and Paulk (2014) had a similar approach to evaluate social validity, but included additional open-ended questions in the form completed by participants. The reported preference for interteaching when compared to lecture has been mixed, with at least some studies reporting student preference for interteaching while others reported preference for lecture even when interteaching was more effective (see Querol, Rosales, & Soldner, 2015 for a review of empirical research on Interteaching including the use of social validity measures).…”
mentioning
confidence: 99%
“…Zayak and Paulk (2014) had a similar approach to evaluate social validity, but included additional open-ended questions in the form completed by participants. The reported preference for interteaching when compared to lecture has been mixed, with at least some studies reporting student preference for interteaching while others reported preference for lecture even when interteaching was more effective (see Querol, Rosales, & Soldner, 2015 for a review of empirical research on Interteaching including the use of social validity measures).…”
mentioning
confidence: 99%
“…Despite the increase in utilizing online learning practices, there appears to be a relative dearth of empirically based studies with a focus on teaching the next generation of researchers and practitioners, using novel online pedagogy within the field of behavior analysis. The pedagogical literature within behavior analysis includes methods for promoting active learning in the face-to-face classroom, under the rubric of such topics as precision teaching, personalized system of instruction, guided notes, response cards, and interteaching (Austin, 2000;Querol, Rosales, & Soldner, 2015).…”
mentioning
confidence: 99%
“…Students rating interteaching as less preferable than standard lecture is unusual in the interteaching literature (see Querol et al, 2015;Saville et al, 2011;Sturmey et al, 2015 for reviews), so it seems likely that the lower preference for interteaching seen in SEC 2 was a result of the modified interteaching method that students experienced. To some extent, this could be due to the modified interteaching session where half of the time was spent in small groups of 2-3.…”
Section: Discussionmentioning
confidence: 99%
“…Since the seminal article by Boyce and Hineline (2002), over 30 studies have been published investigating interteaching and its components (see Querol et al, 2015;Saville et al, 2011b;Sturmey et al, 2015 for reviews). Several modifications of the basic method have since been examined.…”
mentioning
confidence: 99%